1979
DOI: 10.1128/aac.15.6.802
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Methicillin Tolerance in Experimental Staphylococcal Endocarditis

Abstract: Methicillin-tolerant staphylococci are organisms that are inhibited by low concentrations of the drug but are resistant to its bactericidal effects. The clinical significance of this in vitro phenomenon is unknown. An experimental model of staphylococcal endocarditis in rabbits was used to determine whether methicillin-tolerant staphylococci are particularly difficult to eradicate from infected heart valves. In vitro sensitivity testing was used to identify a tolerant and a nontolerant strain of St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

1982
1982
1986
1986

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Media and growth phase of the inoculum are two other significant parameters that vary from experiment to experiment. Several investigators (4,9,10,13,17) have shown that the MBC, and therefore the MBC/MIC ratio, can vary for the same strains of S. aureus, depending on growth media, growth phase of the inoculum, inoculum size, and other factors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Media and growth phase of the inoculum are two other significant parameters that vary from experiment to experiment. Several investigators (4,9,10,13,17) have shown that the MBC, and therefore the MBC/MIC ratio, can vary for the same strains of S. aureus, depending on growth media, growth phase of the inoculum, inoculum size, and other factors.…”
mentioning
confidence: 99%
“…To clarify the relationship between laboratory methodology and tolerance, we determined the minimal bactericidal concentrations and minimal inhibitory concentrations for 20 clinical isolates by two methods. Inocula were prepared by either 3-h growth of the organism in MuellerHinton broth or overnight (22 to 24 h) (4,9,10,13,17) have shown that the MBC, and therefore the MBC/MIC ratio, can vary for the same strains of S. aureus, depending on growth media, growth phase of the inoculum, inoculum size, and other factors.There is growing evidence that the bactericidal effects of cell wall-active antibiotic on bacteria, including S. aureus, can be suppressed in a pH-dependent manner (5,7,11,20,22,23 …”
mentioning
confidence: 99%
“…The P value was 0.01 in four of the six cases and <0.05 in the other two. DISCUSSION In recent years, the relevance of tolerance of S. aureiis strains for the therapeutic response was investigated in various studies (5,6,8,9). Sabath et al (9) Guze et al (6) studied the effect of methicillin upon similar strains in a pyelonephritis model in rats.…”
Section: Methodsmentioning
confidence: 99%
“…The results reported by various authors are somewhat contradictory (2,(5)(6)(7)(8)(9). The question whether infections with tolerant strains are more difficult to treat then infections with susceptible strains can be investigated by means of an experimental infection model in animals.…”
mentioning
confidence: 99%
“…The technical difficulties associated with detecting tolerance are identical to those encountered in MBC determinations. So, tolerance is influenced by the medium (7, 12), incubation time (7,8), growth phase (6,(8)(9)(10), pH value (15), antibiotic carry-over (6,8), as well as by other technical factors (1,8,14). Another characteristic of tolerance is the heterogeneous type of resistance to the lethal effect of the antibiotic.…”
mentioning
confidence: 99%